DESIGN AND OPERATION MODE OPTIMIZATION OF THE DRYING CHAMBER BASED ON ITS 3D MODEL - ОЛЯНИШЕН, ТЕТЯНА; MACHUGA, OLEG (Herald of Khmelnytskyi National University. Technical sciences, 2024)
This paper focuses on the analysis and optimization of the drying chamber design using SolidWorks Simulation software. One of the main problems that arises in the design of drying chambers is the need to ensure optimal conditions for efficient drying of materials. In this regard, this study determines the optimal design parameters of the drying chamber and its operating mode to ensure uniform temperature distribution in the stack. The methodology includes creating a 3D model of the drying chamber and its main components in SolidWorks, generating a difference mesh, conducting a thermal study in SolidWorks Simulation, and applying Design Study to optimize the design parameters of the drying chamber and its operating modes. The simulation results include the output of the heat flow in the stack and temperature measurements at various points, which allows us to assess the temperature differences and the impact of optimization parameters on them. Temperature measurements at different points were performed using the Prob tool, which takes into account the exact geometry and location of nodes on the tetrahedral elements of the difference grid of the 3D model of the drying chamber used for the calculations. In general, the study consists of applying an integrated approach to the design of drying chambers using SolidWorks and automating the optimization process through the SolidWorks API, for which software has been created. The software also allows users to enter input data for the 3D model design and thermal study parameters for their transfer to SolidWorks. In addition, the software provides the ability to perform calculations directly in SolidWorks Simulation but in the background, so that the results obtained will be displayed in a special program window in a fully automated mode. It is also worth noting that performing calculations without visualizing this process significantly reduces the time to obtain results that can be used to improve the technological processes of drying various materials in drying chambers.